Italian validation of the body odor disgust scale - Liuzza, Marco Tullio; Zakrzewska, Marta Z.; Olofsson, Jonas K. (Frontiers in Behavioral Neuroscience, 2024)
Disgust sensitivity to body odors plays a role in a set of psychological mechanisms supposedly evolved to avoid pathogens. To assess individual differences in body odor disgust we previously developed the body odor disgust sensitivity scale (BODS) and validated it in English. The BODS presents six scenarios where disgust could be evoked by smells coming from an internal source and an external source. The present study aimed to validate the BODS in the Italian population and to find further evidence for its structural, construct, and criterion validity. To this purpose, we used two large samples (N = 1050, F = 527; and N = 402, F = 203, respectively) that were representative of the Italian population for sex and age. Across these two studies, we confirmed the hypothesized bi-factor structure, with all the items loading onto a general body odor disgust sensitivity factor, and on two specific factors related to the internal structure. In terms of construct validity, we found that the BODS converged with pathogen disgust sensitivity of the Three-Domains Disgust scale (TDDS) but was distinct from a general propensity to experience negative emotions. The BODS showed criterion validity in predicting the behavioral intentions towards COVID-19 avoidance behavior, although it did not seem to be incrementally valid when compared to the TDDS pathogen subscale. We also established scalar measurement invariance of the BODS regarding gender and found that women display higher levels of BODS, a result consistent with previous literature, and which we discussed in the broader context of cross-cultural and primate findings that points towards a possible evolutionary explanation of this difference.